Plan de marketing para la asociación de productores de café ecológico Lago Agrio (aprocel), del cantón Lago Agrio provincia de Sucumbíos, para el año 2016 - Loayza Romero, Mireya del Cisne (2017)
The Association of Organic Coffee Growers Lago Agrio was created about 10 years ago, since the beginning of its commercial operations has not made a diagnosis to identify the favorable factors that drive the progress of the organization and the unfavorable that slow its growth, Limiting the adoption of strategies to improve their competitiveness. Faced with this situation, it was proposed to carry out a Marketing Plan for the Lago Agrio Ecological Coffee Producers Association (APROCEL), in the canton Lago Agrio province of Sucumbíos, for 2016, through which proposals were made to position the image Of the Association to make more efficient its work of support to the producers of the zone. The study began in the situation assessment in which the internal environment in which it became clear that APROCEL is strong internally analyzed, as achieved a weighted result of 2,84 indicating that the strengths are above weaknesses; in its external environment was determined that opportunities are above threats, this ensures that in view of the matrix EFE APROCEL reached a weighted total of 2,85. The analysis performed the critical factors that affect the success of the organization, classified into opportunities, threats, strengths and weaknesses were identified whose cross allowed set 4 strategies to follow to improve the current situation APROCEL, these are: "Increase capacity technology of APROCEL through the acquisition of an artificial dryer and ecological pulper "; "Providing discounts to companies according to the frequency and quantity demanded of products"; "Set the mark for products sold by the Association so that the client related to the organization"; "It Spread inside and outside the parish social work carried out through APROCEL advertising media" after designing action plans was determined that the budget required for the implementation of the marketing plan amounts to $ 37,565.00; resources that will allow the implementation of the proposal designed to APROCEL, same that will achieve the goals, improving their positioning and profitability.